2013
DOI: 10.1089/jmf.2012.0205
|View full text |Cite
|
Sign up to set email alerts
|

Oral Green Tea Catechins Transiently Lower Plasma Glucose Concentrations in Female db/db Mice

Abstract: Polyphenols, including green tea catechins, are secondary plant compounds often discussed in the context of health-promoting potential. Evidence for such effects is mainly derived from epidemiological and cell culture studies. The aim of the present study was to investigate antidiabetic, antiadipogenic, and anti-inflammatory effects at nonpharmacological doses in an obese diabetic mouse model that exerts early relevant clinical signs of non-insulin-dependent diabetes mellitus. Female db/db mice received a flav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Using a high‐fat diet (HFD)‐induced obesity model, we found that supplementation with EGCG significantly reduced body weight gain, visceral fat weights, and fasting blood glucose level . In db/db mice, a diabetes model, dietary EGCG was found to prevent the progression of glucose intolerance . Many epidemiological studies and short‐term randomized controlled trials (RCT) also showed an association between tea or catechin consumption and lower incidence of metabolic syndrome and diabetes, even though the results are not conclusive .…”
Section: Introductionmentioning
confidence: 98%
“…Using a high‐fat diet (HFD)‐induced obesity model, we found that supplementation with EGCG significantly reduced body weight gain, visceral fat weights, and fasting blood glucose level . In db/db mice, a diabetes model, dietary EGCG was found to prevent the progression of glucose intolerance . Many epidemiological studies and short‐term randomized controlled trials (RCT) also showed an association between tea or catechin consumption and lower incidence of metabolic syndrome and diabetes, even though the results are not conclusive .…”
Section: Introductionmentioning
confidence: 98%
“…One such example of the beneficial effects of green tea consumption is its role in promoting fat oxidation, which is a key preventative of obesity in healthy individuals [3]. Another example of the benefits of green tea consumption is its observed effect in reducing the occurrence of T2D in both laboratory animal studies [4, 5] and clinical studies involving subjects with metabolic syndrome or prediabetes [6, 7] by improving insulin sensitivity and glucose tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it has been demonstrated that flavonoids such as genistein and quercetin, inhibit ATP binding tyrosine kinases and also have the ability to competitively inhibit GLUT-1 through this mechanism [11]. In fact, the effects of flavonoids on glucose absorption and digestion has been the subject of several studies [15][16][17][18]. The inhibitory effect of flavonoids on glucose uptake appears to be already well established, so these compounds have even been suggested for the treatment of diabetes [19][20][21].…”
mentioning
confidence: 99%